2014
DOI: 10.1016/j.amjcard.2013.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Extent of Coronary Atherosclerotic Disease on ST-Segment Changes Induced by ST Elevation Myocardial Infarction

Abstract: The accuracy of the admission electrocardiogram (ECG) in predicting the site of acute coronary artery occlusion in patients with ST-segment elevation myocardial infarction (STEMI) and multivessel disease is not well known. This study aimed to assess whether the presence of multivessel coronary artery disease (CAD) modifies the artery-related ST-segment changes in patients with acute coronary artery occlusion. We reviewed the admission ECG, clinical records, and coronary angiography of 289 patients with STEMI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
2
17
1
Order By: Relevance
“…Also, combining a gain of R-and loss of S-wave in V 1 in one variable seems to be a suitable measurement of the extent of R-waves, since acute ST-segment changes affect the height of R as well as the depth of S. In the clinical setting, lateral wall infarction is specifically due to Cx occlusion. The strong correlation of ST-segment elevation in V 6 in the small group of Cx occlusion and R/S ratio in V 1 was expected considering its laterally located supply area, and is in accordance with earlier studies investigating V 6 ST-segment elevation in single vessel Cx occlusion [16]. However, the correlation between ST-segment elevation in V 6 and R/S ratio in V 1 needs further testing because of underrepresentation of Cx occlusions in STEMI populations.…”
Section: Acute St-segment Changes and R-wavessupporting
confidence: 83%
“…Also, combining a gain of R-and loss of S-wave in V 1 in one variable seems to be a suitable measurement of the extent of R-waves, since acute ST-segment changes affect the height of R as well as the depth of S. In the clinical setting, lateral wall infarction is specifically due to Cx occlusion. The strong correlation of ST-segment elevation in V 6 in the small group of Cx occlusion and R/S ratio in V 1 was expected considering its laterally located supply area, and is in accordance with earlier studies investigating V 6 ST-segment elevation in single vessel Cx occlusion [16]. However, the correlation between ST-segment elevation in V 6 and R/S ratio in V 1 needs further testing because of underrepresentation of Cx occlusions in STEMI populations.…”
Section: Acute St-segment Changes and R-wavessupporting
confidence: 83%
“…Concurrent RV infarction and anterior STEMI may occur in both proximal and distal LAD occlusions. Prior studies have explained some ECG patterns in patients with anterior STEMI that predict the location of LAD occlusion (5,6,17). However, with regard to our findings, this is not true for leads V3R/ V4R.…”
Section: Discussioncontrasting
confidence: 56%
“…Electrocardiography (ECG), which is a noninvasive and fast method to evaluate patients with suspected coronary disease, may provide valuable information about the location of occlusion in LAD artery. Most studies, which have suggested predictive ECG patterns, however, have not included the leads V3R and V4R in their evaluations (4)(5)(6).…”
mentioning
confidence: 99%
“…However, the underlying mechanism of concomitant ST-segment depression and particularly its resolution after PCI in patients with STEMI is highly controversial. It has been speculated that reciprocal ST-segment depression may reflect a more extensive infarction,4 17 18 additional ischaemia beyond the infarct zone,18–21 more diffuse coronary artery disease6 22 or simply a benign mirror projection of the ST-segment elevation without significant clinical relevance 23 24…”
Section: Discussionmentioning
confidence: 99%